2011
DOI: 10.1111/j.1532-849x.2011.00758.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Implant-Abutment Connection Design on Load Bearing Capacity and Failure Mode of Implants

Abstract: Implant-abutment connection design has a significant influence on load bearing capacity and failure mode of implants; however, all implant-abutment connection designs tested would be expected to withstand clinically relevant forces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
46
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(49 citation statements)
references
References 37 publications
1
46
0
2
Order By: Relevance
“…Depending on the solidity of a food, the average bite force ranges from 20 to 120 N 26 . In the present study, a static load of 100 N is applied to simulate an occlusive load, in accordance with previous studies 27,28 .…”
Section: Discussionmentioning
confidence: 91%
“…Depending on the solidity of a food, the average bite force ranges from 20 to 120 N 26 . In the present study, a static load of 100 N is applied to simulate an occlusive load, in accordance with previous studies 27,28 .…”
Section: Discussionmentioning
confidence: 91%
“…Finally, a systematic review on single‐tooth implant restorations reported a 5‐year cumulative incidence of abutment screw loosening of 8.8% . Butt‐joints or slip‐fit joints, indexed external or internal, are still the most widely used connection types in dental implants . Although implants featuring an external hexagon are still widespread in the market, this connection is considered slightly unstable, as a result of horizontal and rotational misfits under loading .…”
Section: Discussionmentioning
confidence: 99%
“…A butt joint only stabilizes the connection between the abutment and the implant fixture by the axial preload of the abutment screw. Occlusal force to the connection is concentrated at the abutment screw; thus, the optimum preload is critical for joint stability . In fact, stability of screw‐type connections is challenged by forces exceeding that of the torqued implant‐abutment system: if occlusal loads exceed the preload, the screw can loosen or break .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…11,12 One of the critical elements influencing the long-term uncompromised functioning of a dental implant is its design. 21,22 Baggi et al 23 investigated the influence of implant diameter and length on stress distribution to calculate the overload risk in crestal bone around the implant neck. [16][17][18][19][20] The implant-abutment connection affects stress distribution in bone.…”
mentioning
confidence: 99%